Updated NLL-SSST-coherence earthquake relocation catalog for the 2020 Mw 6.5 Monte Cristo Range, Nevada earthquake sequence. - Lomax, Anthony (Zenodo, 2021)
CSV catalog and plots of NLL-SSST-coherence earthquake relocations of 17583 events M≥1 2020.01.01 to 2021.08.20 for the 2020 Mw 6.5 Monte Cristo Range, Nevada earthquake sequence. This dataset is an update of the relocations presented in the pre-print article: The 2020 Mw 6.5 Monte Cristo Range, Nevada earthquake: relocated seismicity shows rupture of a complete shear-crack system https://eartharxiv.org/repository/view/1904/ Plots show map, view from south and view from N73E of NLL-SSST-coherence relocations events with error-ellipsoid, semi-major axis ≤ 5 km. Caption (adapted from https://eartharxiv.org/repository/dashboard/1904/ Fig 2): Event color showing hypocenter depth and symbol size proportional to magnitude. Re-picked Mw6.5 hypocenter and its proxy (mean hypocenter of 3 well constrained foreshocks) indicated by small and large, dark red, cross symbols, respectively. SHmin and SHmax show directions of regional minimum and maximum compressive stress, respectively; the intermediate principal stress axis is vertical. Seismic stations shown as dark gray tetrahedrons. Brown lines show faults from the Quaternary fault and fold database for the United States. Background topography image from OpenTopgraphy.org. Red lines show mapped surface ruptures from http://www.nbmg.unr.edu/Geohazards/Earthquakes/MonteCristoRangeEQData.html and https://doi.org/10.1785/0220200371 : DATA AND RESOURCES All relocations performed with USGS-NSL phase arrival picks. The USGS-NSL phase arrival picks accessed from https:// earthquake.usgs.gov (last accessed October 2020). The facilities of IRIS Data Services, and specifically the IRIS Data Management Center, were used for access to waveforms and related metadata used in this study. IRIS Data Services are funded through the Seismological Facilities for the Advancement of Geoscience and EarthScope (SAGE) Proposal of the National Science Foundation under Cooperative Agreement EAR-1261681. The U.S. Geological Survey and Nevada Bureau of Mines and Geology, Quaternary fault and fold database for the United States, is available at: https://www.usgs.gov/natural-hazards/earthquake-hazards/faults (last accessed October 2020). All earthquake relocations were performed with NonLinLoc (http://www.alomax.net/nlloc, https://github.com/alomax/NonLinLoc). SeismicityViewer (http:// www.alomax.net/software, last accessed October 2020) was used for 3D seismicity analysis and plotting, SeisGram2K (http://www.alomax.net/software, last accessed October 2020) was used for seismogram analysis and plotting, ObsPy, (http://obspy.org, last accessed October 2020) for reading seismicity catalogs, EQcorrscan, (https://github.com/eqcorrscan/EQcorrscan, last accessed October 2020) for coherence calculations.